Recurrent Autonomic Dysreflexia due to Chronic Aortic Dissection in an Adult Male with Cervical Spinal Cord Injury - Subramanian Vaidyanathan; Peter L. Hughes; Tun Oo; Bakul M. Soni (The Scientific World Journal)
Autonomic dysreflexia is a hypertensive clinical emergency for persons with spinal cord injury at T-6 level or above. Recurrent autonomic dysreflexia is uncommon in spinal cord injury patients and is usually caused by noxious stimuli that cannot be removed promptly, e.g., somatic pain, abdominal distension. A 61-year-old man, who sustained tetraplegia at C-5 (ASIA-A) 38 years ago, was admitted with chest infection. Computerised tomography (CT) of the chest showed the ascending aorta to measure 4 cm in anteroposterior diameter; descending thoracic aorta measured 3.5 cm. No dissection was seen. Normal appearances of abdominal aorta were seen. He was treated with noninvasive ventilation, antibiotics, and diuretics. Nineteen days later, when there was sudden deterioration in his clinical condition, CT of the pulmonary angiogram was performed to rule out pulmonary embolism. This showed no pulmonary embolus, but the upper abdominal aorta showed some dissection with thrombosis of the false lumen. Blood pressure was controlled with perindopril 2 mg, once a day, doxazosin 4 mg, twice a day, and furosemide 20 mg, twice a day. Since this patient did not show clinical features of mesenteric or lower limb ischaemia, the vascular surgeon did not recommend subdiaphragmatic aortic replacement.